Controlling access to oil roads protects forest cover, but not wildlife communities: a case study from the rainforest of Yasuní Biosphere Reserve (Ecuador). (25th September 2012) - Suárez, E.; Zapata‐Ríos, G.; Utreras, V.; Strindberg, S.; Vargas, J.
Abstract Through the analysis of a case study from Amazonian Ecuador, this paper evaluates the impacts of two oil‐road management approaches on the structure and composition of wildlife communities (large‐ or medium‐sized mammals and game bird species). In a free‐access road, where forest has been cleared and fragmented by colonists, fewer species were found, together with wildlife density estimates that were almost 80% lower than on a control site without human disturbance. In contrast, on the road where access control has been enforced, habitat destruction has been minimal, but several wildlife species showed reductions in their populations, apparently related to changes in the subsistence practices of local Waorani hunters that settled along the road after its construction. In this area, economic subsidies and free transportation from the oil companies, access to the road, more efficient hunting technologies, and market incentives have increased the impacts of hunting by the Waorani, resulting in depletion of the local wildlife populations. Our research suggests that construction of roads in oil extraction areas must be avoided if at all possible. The alternative management of controlling access can be effective for short‐term habitat protection, but not for wildlife conservation, especially when oil industry practices alter the social dynamics of local indigenous groups.